Love of money, FOMO, and self-control in Gen Z financial planning - Kofler, Maximilian (Universitas Pendidikan Nasional, 2025)
Personal financial planning is becoming increasingly important as people become more aware of the need for effective financial management to achieve financial stability and prepare for a better future. This study examines the influence of love of money, Fear of Missing Out (FOMO), and self-control on Generation Z’s personal financial planning, with financial literacy serving as a moderating variable. Using a quantitative approach, data were collected through a structured questionnaire. The study involved 100 Generation Z respondents selected using the Slovin formula. Data were analyzed using SmartPLS 3.0 with path analysis. The findings indicate that love of money, FoMO, and self-control each have a positive influence on personal financial planning. In addition, financial literacy significantly moderates the relationships between love of money and personal financial planning, FoMO and personal financial planning, and self-control and personal financial planning. Based on these results, it is recommended that Generation Z strengthen their financial literacy and develop personal financial plans regularly to support more focused and effective financial management.